The Urban Women Travelling Issue in the Twenty-first Century - Yong Adilah Shamsul Harumain; Nikmatul Adha Nordin; Goh Hong Ching; Noor Suzaini Zaid; Andree Woodcock; Deana Mcdonagh; Komal Faiz (Journal of Regional and City Planning, 2021)
Mobility generally refers to the ability or capacity to move. The subject of women's mobility has been well documented and investigated by researchers since the 1970s. Early studies were initially inspired by the issue of gender-based violence encountered by women. At the same time, there is increasing research on women transportation mobility due to the increasing percentage of women working and travelling outside the house. However, there is an absence of studies that adopted a systematic review of studies related to women's mobility. The increase of women working in the 21st century has led to an increase in the percentage of women travelling, thus engendering issues such as safety, security, mobility and accessibility. This paper attempted to identify studies related to women's mobility in the 21st century from the year 2001 until the year of 2020 by using a systematic literature review, guided by Preferred Reporting Materials for Systematic Reviews and Meta Analyses, also known as the PRISMA Statement, to further understand the scenario of urban women travelling in the global context. This paper reviews previous studies conducted in the 21st century, revealing slight variations of focus among the authors on the urban women travelling issue.Abstrak. Mobilitas umumnya mengacu pada kemampuan atau kapasitas untuk bergerak. Subjek 'Mobilitas Wanita' telah didokumentasikan dan diteliti dengan baik oleh para peneliti sejak tahun 1970-an. Studi terdahulu awalnya terinspirasi dari isu-isu kekerasan berbasis gender yang dihadapi perempuan. Sementara itu, penelitian tentang mobilitas transportasi perempuan semakin meningkat karena meningkatnya persentase perempuan yang bekerja dan pindah ke luar rumah. Namun, belum ada penelitian yang mengadopsi tinjauan sistematis pada artikel terkait studi terkait mobilitas perempuan. Meningkatnya jumlah perempuan yang bekerja di abad ke-21 juga meningkatkan persentase perempuan yang bepergian sehingga menggambarkan banyak masalah antara lain keselamatan, keamanan, mobilitas dan aksesibilitas. Oleh karena itu, tulisan ini mencoba mengidentifikasi kajian-kajian yang berkaitan dengan mobilitas perempuan abad ke-21 dari tahun 2001 hingga tahun 2020 dengan menggunakan Systematic Literature Review yang berpedoman pada Preferred Reporting Materials for Systematic Reviews dan Meta Analysis atau yang lebih dikenal dengan PRISMA Statement untuk memahami lebih jauh skenario perjalanan wanita perkotaan dalam perspektif global. Makalah ini mengulas penelitian sebelumnya yang dilakukan pada abad ke-21 yang telah ditafsirkan dan diuraikan dengan sedikit variasi fokus di antara penulis tentang isu perjalanan wanita perkotaan. Kata kunci. mobilitas wanita, tinjauan literatur sistematis, perjalanan, abad ke-21.